Detection of antibiotic resistance in leprosy using GenoType LepraeDR, a novel ready-to-use molecular test. - Emmanuelle Cambau; Aurélie Chauffour-Nevejans; Liana Tejmar-Kolar; Masanori Matsuoka; Vincent Jarlier (Public Library of Science (PLoS), 2012)
BACKGROUND: Although leprosy is efficiently treated by multidrug therapy, resistance to first-line (dapsone, rifampin) and to second-line drugs (fluoroquinolones) was described worldwide. Since Mycobacterium leprae is not growing in vitro, phenotypic susceptibility testing requires a one year experiment in the mouse model and this is rarely performed. Genetics on antibiotic resistance provide the basis for molecular tests able to detect for antibiotic resistance in leprosy. METHODOLOGY/PRINCIPAL FINDINGS: A reverse hybridization DNA strip test was developed as the GenoType LepraeDR test. It includes DNA probes for the wild-type sequence of regions of rpoB, gyrA and folP genes and probes for the prevalent mutations involved in acquired resistance to rifampin, fluoroquinolones and dapsone, respectively. The performances of the GenoType LepraeDR test were evaluated by comparing its results on 120 M. leprae strains, previously studied for resistance by the reference drug in vivo susceptibility method in the mouse footpad and for mutations in the gene regions described above by PCR-sequencing. The results of the test were 100% concordant with those of PCR sequencing and the mouse footpad test for the resistant strains: 16 strains resistant to rifampin, 22 to dapsone and 4 to ofloxacin with mutations (numbering system of the M. leprae genome) in rpoB (10 S456L, 1 S456F, 1 S456M + L458V, 1 H451Y, 1 G432S + H451D, 1 T433I + D441Y and 1 Q438V), in folP1 (8 P55L, 3 P55R, 7 T53I, 3 T53A, 1 T53V) and gyrA (4 A91V), respectively. Concordance was 98.3% for the susceptible strains, two strains showing a mutation at the codon 447 that in fact was not conferring resistance as shown by the in vivo method. CONCLUSIONS/SIGNIFICANCE: The GenoType LepraeDR test is a commercially available test that accurately detects for antibiotic resistance in leprosy cases. The test is easy to perform and could be implemented in endemic countries.